2010
DOI: 10.1111/j.1468-1331.2010.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral symptoms in ALS are negatively related to caregivers’ burden and quality of life

Abstract: Neurobehavioral symptoms were present in 50% of our ALS patients and were related to bulbar symptoms. They have a profound negative impact on caregivers' psychological status and were highly related with caregivers' burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
114
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 33 publications
8
114
0
4
Order By: Relevance
“…Not only has the ECAS shown high sensitivity and specificity to cognitive impairment against a full neuropsychological battery (17)(18)(19)(20)(21), it has high clinical utility in describing the nature of these impairments. Monitoring progression of cognitive and behavioural symptoms may have important implications for patient management, treatment, prognosis, end-oflife decision making, and caregiver burden (22)(23)(24)(25)(26)(27)(28). The purpose of this study was to develop alternate forms of the ECAS to facilitate repeated assessment and longitudinal monitoring of cognition and behaviour in patients with ALS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only has the ECAS shown high sensitivity and specificity to cognitive impairment against a full neuropsychological battery (17)(18)(19)(20)(21), it has high clinical utility in describing the nature of these impairments. Monitoring progression of cognitive and behavioural symptoms may have important implications for patient management, treatment, prognosis, end-oflife decision making, and caregiver burden (22)(23)(24)(25)(26)(27)(28). The purpose of this study was to develop alternate forms of the ECAS to facilitate repeated assessment and longitudinal monitoring of cognition and behaviour in patients with ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive dysfunction may have important implications for patient management, treatment fidelity, power of attorney, and endof-life decision making (22)(23)(24). Behaviour change has been linked to increased carer burden (25,26) and shortened survival (27,28). As such, the accurate assessment of cognition and behaviour over time is of vital importance to meeting the needs of patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should examine patients with PMA at an early disease stage to assess whether nonmotor changes have an impact on treatment issues, patient-caregiver interaction, and survival duration, similar to ALS. 2,39,40 Also, studies on nonmotor changes in MND should include measures of UMN severity in addition to the ALSFRS-R (which is mostly a lower motor neuron measure) to further confirm the hypothesis that a proportion of patients with PMA may be viewed as having ALS minus detectable UMN signs.…”
mentioning
confidence: 99%
“…Other authors, like Chiò et al also observed the same. 19 Other risk factors associated with greater strain were the carers' age and gender, with women, which represent the majority of caregivers, at higher risk. It seems relevant to refer the fact that, giving the time they spend on taking care of ALS patients, these people tend to ignore their own health condition, which could become a serious problem since older people have a higher risk of disease than younger ones.…”
mentioning
confidence: 99%
“…On the other hand, the later were connected to patient's neurobehavioral symptoms. 19 One important factor associated with lower HRQoL was the use of ventilation on ALS patients. NIV and mechanical ventilation on tracheostomized patients decreased quality of life on family, since they become responsible for the maintenance of the equipment and stability of the patient that is in more advanced stages of the disease.…”
mentioning
confidence: 99%